PENGEMBANGAN MEDIA PEMBELAJARAN E-MAGAZINE SUBMATERI MANFAAT KEANEKARAGAMAN HAYATI KELAS X SMA BERBASIS TUMBUHAN LIAR SEBAGAI SUMBER PANGAN - Hanifa, Hanifa; Syamswisna, Syamswisna (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2024)
Learning media is used to improve the quality of teaching and learning, because using interesting media in lesson can increase the students learning motivation. This study aims to determine the feasibility of E-Magazine media from the results of ethnobotanical studies of wild plants as food sources in Serundung Permai Hamlet I, Melawi Regency. The development of E-Magazine media is carried out to be an additional source of information, especially on the subtopic of the benefits of biodiversity related to wild plants that are used as alternative food sources. The method in this research is to use a qualitative descriptive method consisting of 2 stages of research including interviews and media making. The media-making stage is then broken down into pre-production, production, and post-production. Media feasibility validation was carried out at the post-production stage using a questionnaire with a Likert scale assessment and analyzed using the Lawshe formula. The results of media validation obtained a CVI value of 1.00. The validation results exceeded the 0.99 value criteria from 5 validators, which can be concluded that the E-Magazine media is valid for use on the benefits of biodiversity subtopic.